Unexpected stories eaudiobook Two novellas. - Butler, Octavia E. (Recorded Books Inc., 2018)
This exciting collection presents two previously unpublished stories by SF legend Butler. "A Necessary Being" precedes the events of Survivor, Butler's third (famously disowned) installment in her Patternist series, and includes characters from it, focusing exclusively on the Kohn, aliens who build their social hierarchies on the blueness of their fur. In "Childfinder," a black woman with the gift of identifying children with latent psychic ability refuses to share her skill with an organization of white telepaths.